Industrial vibration and noise analysis of conventional drilling machine on different type of materials - Nur Afiq, Abu Bakar (2007)
Nowadays, machines used everywhere in the industry from the basic level of industry until large industry. These machines as well as drilling machine will produce vibration and noise either in low or high frequency. Using the specific way, the vibration and noise data can be collected and the next step the data can be very useful to control the behavior of the machines. This thesis present the way of collecting the vibration and noise data by using specific software and device. The Pulse LabShop version 11.1 will be used to develop the interface and to obtain the data acquired between computer and the drilling machine by using sensors. The data produces when drilling operation will convert into the velocity spectrum and sound mapping. As a result, the vibration and noise data will be used as the guide to monitor a machine especially in condition monitoring.